Bibliometric analysis of cash waqf / Nurnazifa Gzahli, Hasyeilla Abd Mutalib and Afiffudin Mohammed Noor - Gzahli, Nurnazifa; Abd Mutalib, Hasyeilla; Mohammed Noor, Afiffudin (Universiti Teknologi MARA, Perlis, 2022)
This article presents a bibliometric analysis on cash waqf which have been analysed using the VOSviewer 1.6.18 to evaluate the global research trends, specifically the publication growth, publication outputs by countries, topics of interest, and co-occurrences of author keywords. Approximately 111 articles published between 1979 to 2022 were retrieved from the Scopus database. The findings have shown a growing trend in terms of publication outputs. Most of the publications were by the researchers from Malaysia followed by Indonesia and Turkey. The keyword 'cash waqf' has the highest occurrence in the publications followed by 'waqf.' A closer look at the co-occurrences of author keywords revealed that 'cash waqf' has 24 links. It can be concluded that the results from the analysis could be used by future researchers to explore under research areas related to workplace cash waqf.